2015
DOI: 10.1021/jacs.5b02428
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Fast Catalysis in Allylic Amination Reactions Catalyzed by Pd–Ti Heterobimetallic Complexes

Abstract: Experiments and density functional calculations were used to quantify the impact of the Pd-Ti interaction in the cationic heterobimetallic Cl2Ti(N(t)BuPPh2)2Pd(η(3)-methallyl) catalyst 1 used for allylic aminations. The catalytic significance of the Pd-Ti interaction was evaluated computationally by examining the catalytic cycle for catalyst 1 with a conformation where the Pd-Ti interaction is intact versus one where the Pd-Ti interaction is severed. Studies were also performed on the relative reactivity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 85 publications
1
48
1
Order By: Relevance
“…An emerging area of homogeneous catalysis is the use of bimetallic catalysts featuring two closely associated metal sites . In addition to the “knobs” mentioned above for optimizing single‐site catalysts, these bimetallic systems present, in principle, additional structural elements that can be manipulated to “tune” reactions (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…An emerging area of homogeneous catalysis is the use of bimetallic catalysts featuring two closely associated metal sites . In addition to the “knobs” mentioned above for optimizing single‐site catalysts, these bimetallic systems present, in principle, additional structural elements that can be manipulated to “tune” reactions (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Total yield: 60 mg (92% with respect to 1). 1 (4). To a solution of 1 (70 mg, 0.076 mmol) in pentane (1 mL) was added a solution of PhNCO (9 mg, 0.076 mmol) in pentane (2 mL), dropwise at −35 °C.…”
Section: General Proceduresmentioning
confidence: 99%
“…1 There are a growing number of reports of compounds in which group 4 metal atoms are directly bonded to late transition metals or p-block metals in heteronuclear di-and polynuclear complexes. [2][3][4] Despite this, isolable compounds featuring a metalmetal bonding interaction between two group 4 metals are limited to a handful of examples. 5 We have recently reported the synthesis and isolation of the dititanium bis(pentalene) complex (μ:η 5 ,η 5 -Pn † )2Ti2 (1, Pn † = 1,4-{Si i Pr3}2C8H4), 6 which density functional theory (DFT) studies revealed to have two metalmetal bonds and a low lying metal-based empty orbital.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, heterobimetallic complexes containing early‐ and late‐transition metals (early‐late heterobimetallic complexes, ELHBs) have attracted special interest because they provide vastly different reaction sites that comprised of a hard Lewis acidic early‐transition metal and a soft Lewis basic late‐transition metal, respectively. [2] In addition, the unique nature of ELHBs is highlighted to the covalent bonding[3] and dative bonding[3c][4] character of the metal–metal interaction in ELHBs, and the metal–metal interaction has been widely applied for activating small molecules. [3i][4e – o][5] Such ELHBs involving a metal–metal interaction were categorized into two types of structures: one is a metal–metal bond without any bridging ligand, while the other is a ligand‐bridged metal–metal bonded structure.…”
Section: Introductionmentioning
confidence: 99%